A brief CBT intervention for depersonalisation/derealisation in psychosis: study protocol for a feasibility randomised controlled trial. Issue 1 (December 2016) - Farrelly, Simone; Peters, Emmanuelle; Azis, Matilda; David, Anthony; Hunter, Elaine
Abstract Background Depersonalisation is the experience of being detached or disconnected from one's experience. Studies suggest that clinically significant levels of depersonalisation are common in individuals who have psychotic symptoms and are associated with increased impairment. However, to date, there have been no studies that have investigated an intervention designed to target clinically significant depersonalisation in such patient groups. This study aims to determine the feasibility and acceptability of a brief intervention targeting clinically significant depersonalisation in those who also have current psychotic symptoms. Methods/design The feasibility of delivering six sessions of cognitive behavioural therapy for depersonalisation in psychosis patients will be evaluated using a single-blinded randomised controlled trial with a treatment as usual control condition. Participants will be assessed at baseline and then randomised to either the treatment or control arm. Participants randomised to the treatment arm will be offered six sessions of individual cognitive behavioural therapy delivered over a maximum of 10 weeks. Therapy will focus on an individualised shared formulation of depersonalisation experiences and behavioural, cognitive, emotional regulation and thinking process strategies to decrease distress associated with depersonalisation. Participants will be assessed again at a 10-week (post-randomisation) follow-up assessment. The primary outcomes of interest will be those assessing the feasibility and acceptability of the intervention including rates of referral, eligibility and acceptance to participate; attendance at therapy sessions and completion of homework tasks; satisfaction with the intervention; maintenance of blinding; and therapist competence. Secondary outcomes will be data on clinical outcome measures of depersonalisation and positive symptoms of psychosis, anxiety, depression and post-traumatic stress. Discussion This study will determine the feasibility of delivering six sessions of cognitive behavioural therapy for individuals with current psychotic symptoms who also experience clinically significant levels of depersonalisation. The results will provide information to inform a larger randomised trial to assess intervention efficacy. Trial registration ClinicalTrials.govNCT02427542